PENGARUH GAYA KEPEMIMPINAN, MOTIVASI, DAN LINGKUNGAN KERJA TERHADAP KINERJA PEGAWAI BADAN KEPEGAWAIAN DAERAH DIY - Nuri Ardian Ningsih (JURNAL EKOBIS DEWANTARA, 2018)
This study aims to determine a positive influence between work discipline, motivation, and organizational culture partially on employee job satisfaction PT. Tripatra Engineering Yogyakarta. To know the most dominant factors affect the job satisfaction of employees of PT. Tripatra Engineering Yogyakarta. The variables of this study is the work discipline, work motivation, organizational culture and job satisfaction. The population in this study are employees of PT Tripatra Engineering Yogyakarta totaling 50 people, so the population is less than 100, the authors take the object of research at PT Tripatra Engineering Yogyakarta, where the entire population is used as a research subject and no sample, this study used census method. The method of collecting data using questionnaires. The analysis technique used is multiple linear regression with a significance level of 5%. The results obtained by the equation Y = 0,248X1 + 0,287X2 + 0,445X3. There is a positive and significant influence between the discipline of work on job satisfaction of employees of PT. Tripatra Engineering Yogyakarta, with a significance level of 5%. There is a positive and significant influence between work motivation on employee job satisfaction PT. Tripatra Engineering Yogyakarta, with a significance level of 5%. There is a positive and significant influence of organizational culture on job satisfaction of employee PT. Tripatra Engineering Yogyakarta, with a significance level of 5%. The most dominant factor influencing job satisfaction is the organization's culture. There is a simultaneous influence of labor discipline, motivation and organizational culture on job satisfaction, with a significance level of 5%. Job satisfaction is affected variable work discipline, motivation and organizational culture amounted to 70.1%, while the remaining 29.9% influenced by other factors. Keywords: Work Discipline, Work Motivation, Organizational Culture and Job Satisfaction